Psychedelics meet human brain organoids: insights into proteomics and potential for Alzheimer’s disease treatment - Androni, Xenia; Boyd, Rachel J.; Rosenberg, Paul B.; Mahairaki, Vasiliki (Frontiers in Dementia, 2025)
Alzheimer’s disease (AD) is characterized by a long preclinical phase lasting more than a decade before the onset of its clinical phase of mild cognitive impairment (MCI) or dementia. Recent advances in psychedelic research underscore numerous neuroplastogenic and anti-inflammatory alterations induced by these compounds, making them promising therapeutic candidates for AD. In this mini review, we will briefly summarize the existing literature using human cerebral organoids to study the molecular and metabolic changes caused by various psychedelic compounds, focusing on their potential therapeutic applications for AD.